2010
DOI: 10.4314/njps.v24i2.52910
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, cadmium-induced toxicity, serum biochemical and the histological abnormalities of the kidney and testes of the male wistar rats

Abstract: Summary:The effects of different doses of cadmium (CD) on some biochemical, hormonal and histopathological parameters of the liver, kidney and testes of the Wister rate were investigated. Cadmium (CD) in the dose range 0-40mg/kg while causing a time-and dose-dependent decrease of the basal serum levels of alkaline phosphatese (ALP) also caused a dose-dependent increase in the serum concentration of the acid and prostatic acid phosphatases. The value of the ALP changed from 148.7±1.0 IU/L in the control to 53.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 31 publications
(20 reference statements)
4
43
0
2
Order By: Relevance
“…The present study indicated that the administration of heavy metals to rats produced testicular damage, which led to spermatogenic arrest. Similar observations were noted in experimental animals exposed to heavy metals [29], [30], and [31]. The potential toxicity of heavy metals caused alteration in sperm morphology, count, motility as well as biochemical disruptions of enzymes and hormones [26].…”
Section: Results:-supporting
confidence: 73%
“…The present study indicated that the administration of heavy metals to rats produced testicular damage, which led to spermatogenic arrest. Similar observations were noted in experimental animals exposed to heavy metals [29], [30], and [31]. The potential toxicity of heavy metals caused alteration in sperm morphology, count, motility as well as biochemical disruptions of enzymes and hormones [26].…”
Section: Results:-supporting
confidence: 73%
“…14 The significant alterations in the renal function parameters of Cd exposed animals observed in the present study (Table 1) is in line with the renal toxicity of Cd. 23 It has been observed that Cd induced renal damage is associated with degeneration and hypertrophy of epithelial cells and dialation of glomeruli and massive local haemorrhage of the renal tissues in kidney tubules. 24 The present study however did not include histological examination of various organs, which would have confirmed these changes earlier attributed to Cd toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Twentyseven percent albumin in the young bone is in the tissue fluid and there is about 57% in the calcification matrix, and about 16% is intra-vessel. The whole volume albumin out of vessel in per unit of bone mass is similar to which is in the soft tissue [28,30,31]. The mechanism for decreasing albumin concentration is because of destroying the liver cells following receiving cadmium that this reduction has been neutralized by injecting zinc and then the albumin has returned to its preliminary concentration that indicates zinc has had the preventive effect on cadmium effect.…”
Section: Discussionmentioning
confidence: 65%